Bioversity International Annual Report 2016 - Bioversity International (Bioversity International, 2017)
Bioversity International's annual report looks back at accomplishments in 2016 and highlights research on healthy diets from sustainable food systems, productive and resilient farms and forests, genetic resources conservation and use.